Decolonizing Curriculum through Love and Deep Learning: Toward an Integrative Cognitive, Affective, and Spiritual Framework - Yusgiantara, Akbar; Ibrahim, Rustam (Lembaga Yasin AlSys, 2025)
This study introduces Love Education for Deep Learning as a conceptual framework that redefines education from a technocratic instrument into an ethical and transformative arena. Grounded in cognitive, emotive, and spiritual qualities rooted in mahabbah (love) and rahmah (compassion), the paradigm connects the global movement toward humanistic curricula with decolonial critiques of Eurocentric education. Through conceptual inquiry and systematic narrative synthesis, the study advances three key contributions: it articulates love and deep learning as mutually reinforcing foundations for educational practice; it proposes a triangulated cognitive, affective, and spiritual framework for understanding learning processes; and it establishes the Love Curriculum as an epistemological novelty in curriculum theory. A cycle implementation model is proposed to link education policy, teaching practices, and student outcomes, thereby offering a conceptual roadmap for the implementation of Indonesia’s Merdeka Belajar reform. Although conceptual in nature, this paradigm delineates a research agenda for empirical and cross-cultural investigations on motivation, resilience, and critical thinking, and supports global efforts to rehumanize and decolonize education.